2022
DOI: 10.1007/s10162-022-00874-y
|View full text |Cite
|
Sign up to set email alerts
|

Low Evidence for Tinnitus Risk Factors: A Systematic Review and Meta-analysis

Abstract: Aims/Hypothesis Identifying risk factors for tinnitus could facilitate not only the recommendations for prevention measures, but also identifying potential pathways for new interventions. This study reports the first comprehensive systematic review of analytical observational studies able to provide information about causality (i.e., case–control and cohort designs). Methods A literature search of four electronic databases identified epidemiological studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…A pooled analysis of eleven studies (totaling over 17,000 patients) revealed that the levels of Vit D were significantly lower in patients with both acute (mean difference: −10.6; 95% CI, −19.3 to −2.0) and chronic (mean difference: −3.6; 95% CI, −7.0 to −0.2) otitis media compared to the healthy control population, yielding to a pooled mean difference of −6.26 (95% CI, −10.5 to −2.0) in all patients with otitis media. Such relationship between low Vit D and otitis media may hence justify a concomitantly increased risk of developing tinnitus, as shown in the meta-analysis published by Biswas et al [ 23 ], who concluded that patients with otitis media have an over 60% enhanced risk of developing tinnitus (relative risk [RR], 1.63; 95% CI, 1.61–1.65). Besides otitis, low Vit D levels may also be causally associated with benign paroxysmal positional vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…A pooled analysis of eleven studies (totaling over 17,000 patients) revealed that the levels of Vit D were significantly lower in patients with both acute (mean difference: −10.6; 95% CI, −19.3 to −2.0) and chronic (mean difference: −3.6; 95% CI, −7.0 to −0.2) otitis media compared to the healthy control population, yielding to a pooled mean difference of −6.26 (95% CI, −10.5 to −2.0) in all patients with otitis media. Such relationship between low Vit D and otitis media may hence justify a concomitantly increased risk of developing tinnitus, as shown in the meta-analysis published by Biswas et al [ 23 ], who concluded that patients with otitis media have an over 60% enhanced risk of developing tinnitus (relative risk [RR], 1.63; 95% CI, 1.61–1.65). Besides otitis, low Vit D levels may also be causally associated with benign paroxysmal positional vertigo.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the relationship between migraine, tinnitus, and cerebral blood flow patterns suggests that migraine may worsen the underlying mechanisms of chronic tinnitus, emphasizing the relevance of migraine treatment (32). Identifying risk factors for tinnitus, including hearing-related and nonotological factors, underscores the significance of addressing these factors in treatment and prevention, potentially reducing its co-occurrence with migraine (33). Taken together, these studies emphasize the potential benefits of integrating migraine treatment strategies into tinnitus management, considering the shared pathophysiology and symptom overlap between the two conditions (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Despite its high prevalence and debilitating consequences [ 2 ], the available epidemiological data on its risk factors are inadequate. Above all, there is a distinct paucity of large, well-conducted analytical studies, i.e., case-control or cohort studies, that quantify the association between putative risk factors and the onset of tinnitus [ 2 , 3 ]. Currently, tinnitus management often involves education and counselling, with a general recommendation of a healthy diet; modifiable lifestyle risk factors for tinnitus, of which diet is an example, should be identified and addressed to prevent and manage tinnitus symptoms [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, tinnitus management often involves education and counselling, with a general recommendation of a healthy diet; modifiable lifestyle risk factors for tinnitus, of which diet is an example, should be identified and addressed to prevent and manage tinnitus symptoms [ 4 ]. In a recent systematic review and meta-analysis of tinnitus risk factors, Biswas and colleagues [ 3 ] revealed the scant evidence on exposures causally related to tinnitus. The review found hearing loss, temporo-mandibular joint disorder, depression, chronic obstructive pulmonary disease, and hyperlipidaemia to be tinnitus risk factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation